Species identity of Gambusia (Pisces: Poeciliidae) introduced to Slovenia - Paul Veenvliet (Natura Sloveniae)
On the basis of morphology of the gonopodium and fin ray counts it was determined that the introduced mosquitofish in Slovenia belong to the species Gambusia holbrooki Girard, 1859 rather than G. affinis (Baird & Girard, 1858). This finding is in accordance with European literature sources but not with Slovene literature, where both taxa are lumped together.